E-commerce dynamic attraction via hybrid value chain to boost supply and fulfil demand: companion and hospitality services platform - Wan Ab Rahman, Nurhayati; Zainuri, Nur Nabilah; Khairol Anwar, Hanis Amira; Mohd Azmi, Siti Nuraishah (HBRP Publication, 2022)
Survival and rise up again are critical after we have experienced Covid-19 pandemic which has affected life of the world population and demolished economy. Living in restriction of physical movement has slowed down many daily activities and common practices including to buy groceries and needs. Alternatively, e-commerce growth has emerged as unprecedented phenomenal in giving hope to the world to fulfil their needs and have better impact to economy and social. This paper introduces a framework of e-commerce dynamic attraction through hybrid value chain to boost supply and fulfil demand. The important framework highlights eight elements; impactful innovation, niche market, disrupt industry, productmarket fit, sustainable business model, supply-driven, e-commerce platform and demandoriented. This contribution is to inspire e-commerce stakeholders to achieve more in sustaining business with better plan, wise strategy and clever business decision. Implication of Covid-19 to lifestyle and economy, e-commerce as the solutions to boost daily activities and economy also being discussed. As a case study, we developed an e-commerce platform that provide solution of providing companion and hospitality services to our targeted early adopters, they are elderly who frequently go to hospital and handy housewives to go for shopping.